Norbert Ksantenskiy i sv. Avgustin. K voprosu ikonografii miniatyury v rukopisi «Vita beati Norberti» iz sobraniya Bavarskoy gosudarstvennoy biblioteki/Норберт Ксантенский и св. Августин. К вопросу иконографии миниатюры в рукописи «Vita beati Norberti» из собрания Баварской государственной библиотеки - Zotova, Yelizaveta Valentinovna (Observatoriya kul'tury, 2014)
The article is devoted to the study of the only surviving illuminated manuscript of the life of Norbert of Xanten. The author analyzes the iconography of the miniature from this manuscript, compares it with miniatures and other illuminated lives of the holy archbishops, manuscripts of the works of St. Augustine, created in Germany in the same period (XII century).
Keywords: 👤 norbert of xanten

Rhetorics of Sanctity: Christina of Hane in the Early Modern Period with a Comparison to a Mary Magdalene Legend - Kirakosian, Racha (Oxford German Studies, 2014)
This study presents the particular case of the medieval mystic Christina of Hane in the Early Modern transmission to uncover the dynamics of sanctity across traditional period boundaries. It discusses the interest of copying and transmitting the Life of this local saintly figure with a legend on Mary Magdalene’s conversion in the sixteenth century. Christina of Hane’s medieval Life becomes refashioned in a seventeenth-century Flemish text that addresses the religious needs of its time, stressing apolitical forms of devotion such as prayers for the souls in purgatory.
Keywords: 👤 christina of hane

Složení a degradace omítek historického objektu Kláštera Želiv - Rezek, P.; Martinec, P. (Koroze a ochrana materialu, 2014)
Composition and degradation of plasters from the historical Želiv monastery. Příspěvek se zabývá charakteristikou omítek odebraných v historickém objektu Kláštera Želiv. Cílem tohoto výzkumu bylo získat informace o původních surovinách a stanovit druh poškození na fasádě zkoumaného objektu. Bylo použito zejména termické analýzy a infračervené spektrometrie, jež umožňují identifi kovat materiály pojiv, v některých případech i pomoci určit druh jejich poškození (resp. zasolení). Byly zkoumány 4 vzorky pojiv omítek. Analýzy historických omítek mohou případně v budoucnu napomoci vyhledat a aplikovat kompatibilní hmotu. Byly kvalitativně i kvantitativně stanoveny primární složky odebraných omítek a stanoveny hlavní příčiny jejich degradace. Komplexní hodnocení složení a degradace omítek vyžaduje využití široké škály analytických metod.
Keywords: želiv

Les incroyables trésors de la chapelle Saint-Blaise (Le Parisien, 2014)
Keywords: silly-tillard

Which is the Greatest - Kirakosian, Racha (Medieval Mystical Theology, 2014)
This paper deals with the medieval theological debate on the primacy of knowledge, love, or enjoyment of God by comparing the biography of the Premonstratensian nun Christina of Hane with the German mystical writings of the Dominican preacher and scholar Meister Eckhart. It shows the ways in which female vernacular thought engaged with a primarily scholastic and male-dominated debate and suggests a performative understanding of the female mystical account. Challenging existing presumptions about Christina’s mystical biography as being inconsistent and composed by several authors, the results of this research demonstrate to what extent the text can still be considered cohesive when discarding gender specified authorial conceptions which cannot be determined in this case.
Keywords: 👤 christina of hane

Future of Park Abbey Windows Unclear (Vidimus, 2014)
Keywords: park

Leiston: Are these the bones of devil dog, Black Shuck? - Potter, Tom (The East Anglian Daily Times, 2014)
Keywords: leiston

Sept-Fontaines : l'abbaye des Sept-Fontaines a traversé près de dix siècles d'histoire - Menvielle, Virginie (La Semaine des Ardennes, 2014)
Keywords: septfontaines en thiérache

L'abbaye Notre-Dame de Septfontaine - Theret, Jacques (Chez nous, 2014)
Keywords: septfontaines en thiérache

Archeologists to revisit medieval site for second ‘crowdfunded’ dig - Potter, Tom (The East Anglian Daily Times, 2014)
Keywords: leiston

De la circulation des "locis sanctis" - le Mons Sion à Prague - Benešovská, Klára (Convivium, 2014)
In 1143, a Premonstratensian abbey with a church dedicated to Mary was founded on Prague's Strahov hill, and the place was called Mons Sion. One of its founders was Jindřich Zdík, a Moravian bishop, who had been a member of the chapter of the Holy Sepulchre in Jerusalem in 1137-38. After returning to Bohemia, Bishop Zdik worked to implement church reforms with the help of regular canons and, later, assistance from the Premonstratensians from Steinfeld. Mons Sion evoked Jerusalem not only through its placement and dedication, but also through its monumental architecture without decoration: its plainness, displaying without distraction the building's harmonious proportions and technically perfect construction, was a response to the proclaimed reforms. the workshop of the abbey played a major role in the twelfth-century building boom of Romanesque Prague. The route of the Palm Sunday pilgrimage processions between the Přemyslid castle and Strahov also confirmed the importance of Mons Sion. The pilgrimages were patterned after the Jerusalem processions between the Holy Sepulchre and Mount Zion. Mons Sion, the Přemyslid castle and the Knights of St. John thus formed a symbolic triangle on the left bank of Vltava river, connected by a new stone bridge to the settlement of the right bank and the other Přemyslid residence, Vyšehrad.
Keywords: strahov

Schrift- und Schreibmystik. Christina von Hane - Suerbaum, Almut M. V. (Oxford University, 2014)
The subject of my thesis is a little-studied hagiographical work that gives important insights into rewriting processes and their significance in medieval textual culture. The anonymous Life of Christina of Hane, a thirteenth-century Premonstratensian nun from the Palatinate, is an example of bridal
Keywords: 👤 christina of hane

Bibliotheca Laureshamensis – Digital: Virtuelle Klosterbibliothek Lorsch (2014)
Keywords: lorsch

Von Krautgärten, Äckern, Gülten und Hühnern: Studien zur Besitz- und Wirtschaftsgeschichte des Prämonstratenserstifts Adelberg im Mittelalter 1178 - 1535 - Albus-Kötz, Stefanie (Schriften zur südwestdeutschen Landeskunde, 2014)
Keywords: adelberg

Zur Sachkultur im Prämonstratenser-Stift Jerichow vor der Auflösung des Konvents im 16. Jahrhundert - Alper, Götz (Mitteldeutschland im Zeitalter der Reformation, 2014)
Keywords: jerichow

Premontrei prépostságok a középkori Magyarországon, különös tekintettel a Kaposfői Szent Benedek prépostságra - Aradi, Csilla M. (A Kaposvári Rippl-Rónai Múzeum Közleményei, 2014)
Keywords: kaposfő; 🇭🇺 hungary (general)

Premontrei monostor feltárása Bárdudvarnokon - Aradi, Csilla M.; Molnár, István (Archaeologia - Altum Castrum Online, 2014)
Keywords: kaposfő

Zum steten frommen Andenken an das 700jährige Jubiläum des Prämonstratenser-Reichsstifts Schussenried - Beck, Paul A. (Diözesan-Archiv von Schwaben : Organ für Geschichte, Altertumskunde, Kunst und Kultur der Diözese Rottenburg und der angrenzenden Gebiete, 2014)
Keywords: schussenried

Die neuesten Ergebnisse über den Dom zu Riga - Bergholde, Agnese (Beiträge zur Tagung vom 1. und 2. September 2011, Backsteinfunde der Archäologie, Beiträge zur Tagung vom 6. und 7. September 2012, Klosterformat und Klöster, 2014)
Keywords: rīga

Seals of Moravian Premonstratensian canonries in the period from the second half of the fifteenth century until the end of the sixteenth century - Bolom-Kotari, Martina (Analecta Praemonstratensia, 2014)
Keywords: 🇨🇿 czechia (general)

Hane, St. Maria, Augustinerchorherrenstift, später Prämonstratenserinnenstift - Burkhart, Ulrich; Heberer, Pia (Pfälzisches Klosterlexikon, 2014)
Keywords: hane

Prémontré's Ordestatuten 1505, 1509 gedrukt - Coppens, C. (Bibliotheek van de Abdij van Park, 2014)
Keywords: ⚖️ chapters and statutes

Az ócsai református (egykor premontrei) templom építéstörténetének vázlata - Csoltkó, Emese (A múltnak kútja: Fiatal középkoros régészek V. konferenciájának tanulmánykötete, 2014)
[Sketches to the Building History of the Calvinist (Former Premonstratensian) Church of Ócsa]
Keywords: ócsa

Du temps où les Prémontrés s'implantèrent en Pays Basque - Duvert, Mikel (Terres de Navarre, 2014)
Keywords: 🇪🇸 spain (general); 🇫🇷 france (general)

Écrire à Verdun au XIIIe siècle. Le cartulaire de l'abbaye prémontrée Saint-Paul de Verdun. Approche codicologique et paléographique - Évrard, Jean-Pol (L'écrit et le livre peint en Lorraine, de Saint-Mihiel à Verdun (IXe-XVe siècles), 2014)
Keywords: verdun

Die Prämonstratenserpropstei St. Jakob im Prättigau ca.1222–1526 - Fischer, Albert (Brennpunkte der Geschichte der Klöster im Bistum Chur in seinen alten Grenzen (bis 1816): Aufgelöste oder aufgehobene Konvente, 2014)
Keywords: prättigau

A Privilege of Pope Innocent III for the Premonstratensian House of Bellpuig de les Avellanes - Freedman, Paul; Smith, Damian (Römische Historische Mitteilungen, 2014)
Siglenverzeichnis Bericht des Historischen Instituts beim Österreichischen Kulturforum in Rom für das Studienjahr 2011/2012 Astrid Larcher - Manuele Laimer, Ascoli Satriano, Gianera Piccola. Vorbericht zu den Grabungskampagnen 2010-2012 Paul Freedman - Damian Smith, A Privilege of Pope Innocent III for the Premonstratensian House of Bellpuig de les Avellanes Rudolf S. Stefec, Die Überlieferung der Deklamationen Polemons Petr Maťa, The false Orsini from over the Alps: Negotiating aristocratic identity in late medieval and early modern Europe Tomáš Černušák, Die Böhmische Kammer als Thema der Prager Nuntiatur zu Beginn des 17. Jahrhunderts Alessandro Metlica, Il Parnasso dell `Istro. Eugenio di San Giuseppe, Caramuel y Lobkowitz e la prima accademia italiana di Vienna (1657) Péter Tusor, Kardinalsnominierungen durch das Haus Habsburg im 17. Jahrhundert Rita Tolomeo, Potenze Protetrici e Unionismo nelle Terre Bulgare Andreas Gottsmann, "Warum lässt uns der Hl.Stuhl im Stich?" Die vatikanische Haltung zur Regierung Schuschnigg hinsichtlich Restauration und staatlicher Selbstständigkeit Inge Podbrecky, Gio Ponti in Wien. Das italienische Kulturinstitut im Palais Lützow-Fürstenberg Zusammenfassungen
Keywords: bellpuig de las avellanes

El monasterio premostratense de Santa María de La Vid durante los siglos XIV y XV: formas de explotación del dominio - Fuertes, Maria Teresa Angulo (Espacio Tiempo y Forma. Serie III, Historia Medieval, 2014)
En el presente artículo analizamos la evolución de las formas de explotación del dominio de un importante monasterio premostratense castellano, el de Santa María de La Vid, durante la baja Edad Media. En el siglo XV cambia la dinámica económica del cenobio que pasa de administrar directamente sus granjas a darlas a censo enfitéutico, bien a particulares, bien a los concejos de los lugares en los que se encontraban ubicadas. Se analizan las razones de este cambio y se compara esta evolución con la de otros monasterios y conventos peninsulares así como las razones que los diferentes estudiosos señalan para esta transformación en la forma de organización económica de los cenobios mencionados.This article examines the evolution of various forms of domain management by an important Castilian Premonstratensian monastery, Santa María de la Vid, during the late Middle Ages. During the fifteenth century an important economic shift takes place as the monastery relinquishes direct management of its domains and leases the land through emphyteutic tenure either to individuals, or to the town councils located near their land. The reasons for this change will be examined. Morevoer, the development of this phenomenon will be compared to that of other Peninsular monasteries and convents. Finally, the motives given by specialists for the shift in economic organization of these monasteries will be assessed.
Keywords: la vid

Visitationsrecht des Abts Leonard Dürr von Adelberg über die Prämonstratenser-Ordensprovinz Schwaben 1518 - Giefel, Joseph Anton (Diözesan-Archiv von Schwaben : Organ für Geschichte, Altertumskunde, Kunst und Kultur der Diözese Rottenburg und der angrenzenden Gebiete, 2014)
Keywords: adelberg; 🇩🇪 germany (general)

‘Ante omnia, fratres carissimi, diligatur Deus, deinde proximus’: Herman/Judah’s Opusculum de conversione sua Re-examined - Hames, Harvey J. (Conﬂict and Religious Conversation in Latin Christendom: Studies in Honour of Ora Limor, 2014)
Keywords: 👤 hermann of cologne

Neue Untersuchungen im Süd-West-Flügel der Prämonstratenserabtei Speinshart (Lkr. Neustadt a. d. Waldnaab) - Heidenreich, Anja (Beiträge zur Archäologie in der Oberpfalz und in Regensburg, 2014)
Keywords: speinshart

De graven en grafmonumenten van graaf/rooms-koning Willem II en Floris de Voogd in het koor van de abdijkerk Middelburg - Henderikx, Peter A. (Archief: mededelingen van het Koninklijk Zeeuwsch Genootschap der Wetenschappen, 2014)
Keywords: middelburg

Neues vom untergegangenen Prämonstratenserstift Heiligenberg bei Bruchhausen-Vilsen - Hucker, Bernd Ulrich (Althannoverscher Volkskalender, 2014)
Keywords: heiligenberg

Getuigenissen van een groots verleden. Materiële sporen van de Antwerpse Sint-Michielsabdij - Janssens, Herman (Bijdragen van de contactdag, 2014)
Keywords: antwerp

Manuscript Work of the Zwierzyniec Norbertine Nuns of the Seventeenth and Eighteenth Century - Kaczor-Scheitler, Katarzyna (Analecta Praemonstratensia, 2014)
Keywords: zwierzyniec

Die Prämonstratenser-Stiftskirche Jerichow und der frühe Backsteinbau in der Altmark und im Jerichower Land - Kaufmann, Damian (Beiträge zur Tagung vom 1. und 2. September 2011 Backsteinfunde der Archäologie; Beiträge zur Tagung vom 6. und 7. September 2012 Klosterformat und Klöster, 2014)
Keywords: jerichow

Poutní a farní chrám Páně Jména Panny Marie ve Křtinách - Kavička, Karel (Kartuziánské nakladatelství, 2014)
Keywords: křtiny

Kleinbockenheim, St. Martin, Propstei "Auf dem Berg" des Prämonstratenserstifts Wadgassen - Keddigkeit, Jürgen; Lagemann, Charlotte (Pfälzisches Klosterlexikon, 2014)
Keywords: kleinbockenheim

Enkenbach, St. Maria, Prämonstratenserinnenstift, später Prämonstratenserpropstei - Keddigkeit, Jürgen; Untermann, Matthias (Pfälzisches Klosterlexikon, 2014)
Keywords: enkenbach

Kaiserslautern, St. Maria, Hospitalkloster, später Prämonstratenserstift bzw. -kloster, dann Kollegiatstift St. Marien und St. Martin - Keddigkeit, Jürgen; Wenz, Martin; Untermann, Matthias (Pfälzisches Klosterlexikon, 2014)
Keywords: kaiserslautern

Premontrei breviárium és collectionale – Premonstratensian Breviary and Book of Collects - Knapp, Eva (Kép és kereszténység = Image and Christianity, 2014)
Keywords: 📚 premonstratensian (general)

Premonstrátský klášter Louka u Znojma v době předbělohorské (1526-1620) - Kohoutek, Michael (Masaryk University, 2014)
Keywords: louka

Festsaal und Abtei des Klosters Weißenau - Krins, Hubert (Denkmalpflege in Baden-Württemberg : Nachrichtenblatt der Landesdenkmalpflege, 2014)
Keywords: weissenau

Archeologische begeleiding Woldjerweg 3 en 5 te Wittewierum, gemeente Ten Boer (GR) - Krol, T.N. (DANS Data Station Archaeology, 2014)
Keywords: bloemhof

Børglum domkirke og kloster i middelalderen - Krongaard Kristensen, Hans (Vendsyssel Historiske Museum, 2014)
Keywords: børglum

De abdij van Park en haar historische bibliotheek - Lani, Stefan van (Bibliotheek van de Abdij van Park, 2014)
Keywords: park

Kriegswahrnehmung und Friedensbemühung bei den frühen Prämonstratensern - Leinsle, Ulrich Gottfried (Friedensethik im frühen Mittelalter: Theologie zwischen Kritik und Legitimation von Gewalt, 2014)
Keywords: 📚 premonstratensian (general)

Die Puchberger und das Prämonstratenserstift Osterhofen - Lickleder, Hermann ("... und es hat doch was gebracht !" Festschrift für Karl Schmotz zum 65. Geburtstag, 2014)
Keywords: osterhofen

Quellen zur Geschichte des Stiftes Flaesheim im 13. Jahrhundert (III) - Lindken, Theodor; Schwabe, Gabriele (Vestische Zeitschrift, 2014)
Keywords: flaesheim

Thomas Son of Gospatric and the Premonstratensian Canons of Preston Patrick & the Nature of Shap Abbey's Link with the Westmorland Township After c.1201 to 1540 - Lucas, Peter (PJYL Publishing, 2014)
Keywords: preston patrick; shap

Súkromný archív Leleského konventu z pohľadu stredovekej diplomatiky - Maretta, Robert Gregor (Historia Ecclesiastica, 2014)
Keywords: leles

Évolution et signification des accensements perpétuels et viagers de l'abbaye d'Humilimont (1250-1350) - Morard, Nicolas (Mémoires de la Société pour l'histoire du droit et des institutions des anciens pays bourguignons, 2014)
Keywords: humilimont

Kirche oder Schloss?: das frühere Prämonstratenserkloster Mildenfurth bei Wünschendorf - Nagel, Franz (Heimat Thüringen, 2014)
Keywords: mildenfurth

Pokračování výzkumu v areálu premonstrátské kanonie v Teplé - Nováček, Karel; Široký, Radek; Starková, Lenka (2014)
Keywords: teplá

Der "ordinarius loci" als Problem: Bischof Embricho von Würzburg und die Anfänge der Prämonstratenserstifte Oberzell, Veßra und Tückelhausen - Petersen, Stefan (Jahrbuch für fränkische Landesforschung, 2014)
Keywords: oberzell; tückelhausen; veßra

Die Rechtsstellung des Prämonstratenserinnenstifts Hausen gegenüber Bischof, Vogt und Vaterabt - Petersen, Stefan (Mainfränkisches Jahrbuch für Geschichte und Kunst, 2014)
Keywords: hausen

Fast 800 Jahre Marienverehrung: das Kloster Maria Engelport ist ein seit Jahrhunderten bekannter Wallfahrtsor - Pies, Norbert J. (Jahrbuch für den Kreis Cochem-Zell, 2014)
Keywords: engelport

Nález stredovekého pečatidla hodnoverného miesta jasovského konventu premonštrátov z konca 13. storočia - Ragač, Radoslav (Studia historica Tyrnaviensia, 2014)
The discovery of a late 13th-century seal of authentication at Jasov Premonstratensian convent
Keywords: leles

The foundation by King Wladyslaw Jagiello of the Premonstratensian Abbey in Nowy Sacz and the role of John the Eremit - Rajman, Jerzy (Analecta Praemonstratensia, 2014)
Keywords: nowy sącz

Middeleeuwse muurschilderingen in de Bergkerk in Deventer - Rijn, Elselien van (Analecta Praemonstratensia, 2014)
Keywords: deventer

Rodungsinsel, Kloster, Raststation: die Ausgrabungen des hochmittelalterlichen Klosters Elisabethenzell - Rosmanitz, Harald (Bayerische Archäologie, 2014)
Keywords: einsiedel

Kirchliche Gebäude „Auf dem Berg“ in Niedergründau - Rückriegel, Erwin (Zentrum für Regionalgeschichte (Gelnhausen). Mitteilungsblatt, 2014)
Keywords: niedergründau

Klöster in Oberschwaben: Wiblingen, Schussenried, Ochsenhausen - Sandtner, Claudia (Kunstführer, 2014)
Keywords: schussenried

Gommersheim, St. Maria und Johannes Ev., Prämonstratenserinnenkloster - Schnabel, Berthold; Werling, Michael (Pfälzisches Klosterlexikon : Handbuch der pfälzischen Klöster, Stifte und Kommenden, 2014)
Keywords: gommersheim

Kloster und Wissen - die Arnsteinbibel und ihr Kontext im frühen 13. Jahrhundert - Schonhardt, Michael (Reihe Septem, 2014)
Keywords: arnstein

Monuments in linen: a thirteenth-century embroidered catafalque cover for the members of the Beata Stirps of Saint Elizabeth of Hungary - Seeberg, Stefanie (Dressing the Part: Textiles as Propaganda in the Middle Ages, 2014)
Keywords: altenberg

Textile Bildwerke im Kirchenraum: Leinenstickereien im Kontext mittelalterlicher Raumausstattungen aus dem Kloster Altenberg/Lahn - Seeberg, Stefanie (Studien zur internationalen Architektur- und Kunstgeschichte, 2014)
Keywords: altenberg

L'abbaye de Lieu-Restauré, Un demi-siècle de sauvegarde et de restauration - Smajda, Philippe (Histoire médiévale et archéologie, 2014)
Keywords: lieu-restauré

Renaissance de La Grange de Durance - Trézéguet, Jean-Louis (Revue de l'Agenais, 2014)
Keywords: durance

Bibliotheek van de Abdij van Park - Van Bragt, Jozefa (Peeters, 2014)
Keywords: park

.. tho memorie vor dat semptlikegeschlechte ... Stiftisches Leben und religiöser Alltag adeliger Konventualinnen aus der Familie von Backem-Unverzagt im Frauenkonvent Stoppenberg - Vauseweh, Arno; Vauseweh, Ramona (Vestische Zeitschrift, 2014)
Keywords: stoppenberg

Působení premonstrátů v Litomyšli v době biskupství (1344-1421) - Večeře, Vojtěch (Pomezí Čech, Moravy a Slezska : sborník prací ze společenských a přírodních věd, 2014)
Keywords: litomyšl

Necessary Priests and Brothers: Male-Female Cooperation in the Premonstratensian Women’s Monasteries of Füssenich and Meer, 1140-1260 - Wolbrink, Shelley Amiste (Partners in spirit : women, men, and religious life in Germany, 1100-1500, 2014)
Keywords: füssenich; meer

L'abbaye du Mont-Saint-Martin - Woznicki, Éric (Éd. Communauté de communes du pays du Vermandois, 2014)
Keywords: mont-saint-martin

Kostol Nanebovzatia Panny Márie v Šahách. Od výstavby stredovekého kostola k výstavbe novovekého - Žažová, Henrieta (Studia historica Tyrnaviensia, 2014)
Die Mariä-Himmelfahrt-Kirche in Šahy. Vom Aufbau der mittelalterlichen Kirche bis zum Aufbau des neuzeitlichen Sakralhaus
Keywords: šahy

Selbolder Regesten : zur Geschichte von Reichsgericht und Stift Selbold in den Jahren 1108-1598 unter besonderer Berücksichtigung der Pfarrei Gelnhausen - Zieg, Michael (Verlag Dr. Kovač, 2014)
Keywords: selbold